Strategi Mencapai Kebermaknaan Pembelajaran Bahasa Arab Pada Anak Usia Dini - Nginayatul Khasanah (Universitas Cokroaminoto Yogyakarta, 2021)
Early childhood is called the golden age in the growing period of the child. Early childhood means children aged 0-6 years. At this time children growth rapidly and through the learning process, one of them was language learning as a means of communication. Arabic languange for Indonesian children is a foreign language so there found are various problems. That problems is the meaningless of arabic learning for children. So kindergarten and TPA / TPQ as institutions of early childhood education play an important role in implementing strategies learning. Meaningful Arabic learning for early childhood can be achieved by implementing the right strategy, including the selection materials, media and methods according to the early childhood development stage such as learning while playing. It is based on Carl Rogers and David Ausubel's theory of meaningful learning.